2012
DOI: 10.1002/elps.201200031
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in‐gel protein separation techniques commonly used for fractionation in mass spectrometry‐based proteomic profiling

Abstract: Fractionation of complex samples at the cellular, subcellular, protein or peptide level is an indispensable strategy to improve the sensitivity in mass spectrometry-based proteomic profiling. This study revisits, evaluates, and compares the most common gel-based protein separation techniques i.e., 1-D SDS PAGE, preparative 1-D SDS PAGE, isoelectric focusing in immobilized pH gradients (IEF-IPG), and 2-D PAGE in their performance as fractionation approaches in nanoLC-ESI-MS/MS analysis of a mixture of protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 67 publications
0
27
0
1
Order By: Relevance
“…Although, the classical 2D approach is a golden standard for comparative proteomic analysis, it has some intrinsic limitations e.g., high percentage of gel-to-gel variations (16)(17)(18). To overcome the limitations of classical 2DE, the use of DIGE has been recommended (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Although, the classical 2D approach is a golden standard for comparative proteomic analysis, it has some intrinsic limitations e.g., high percentage of gel-to-gel variations (16)(17)(18). To overcome the limitations of classical 2DE, the use of DIGE has been recommended (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Jafari et al. compared gel‐based protein separation techniques, including SDS‐PAGE, IEF‐IPG, and 2D‐PAGE, for their ability to serve as fractionation techniques for MS analysis of a complex protein sample . They reported that SDS‐PAGE yielded the highest number of identifiable proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The most common protein fractionation techniques can be divided into two main categories: gel‐based and gel‐free. Gel‐based techniques include all types of 1DE and 2DE: SDS‐PAGE, nondenaturing PAGE, and IEF using IPG gel strips . Gel‐free fractionation, commonly used in proteomics, applies distinct liquid‐phase chromatographic methods such as RP, SEC, IEC, affinity chromatography , and IEF .…”
Section: Prefractionation Methodsmentioning
confidence: 99%